INTEGRATED CLINICAL AND GENETIC APPROACH FOR DIAGNOSIS OF RETT SYNDROME IN CHILDREN - I.Yu. Yurov; S.G. Vorsanova; V.Yu. Voinova- Ulas; P.V. Novikov; Yu.B. Yurov (Вопросы современной педиатрии, 2007)
Rett syndrome represents one of the most important neuropsychiatric genetic diseases. It affects generally girls with the incidence 1:10000–1:15000. Mutations in clinked gene mecp2 are considered as the main cause of the disease. The particular patterns of chromosome x replication (type C) are observed in affected females allowing the cytogenetic technique application for the diagnosis. Cytogenetic and molecular genetic studies carried out in the present work allowed us to propose an integrated approach for the diagnosis of this disease. A clinical description, cytogenetic analyses (assessment of an abnormal chromosome X replication type in affected females as well as chromosome complement abnormalities in affected males), molecular cytogenetic assays using DNA probes specific for mecp2 gene region, studying mecp2 mutations, and x chromosome inactivation pattern studies were combined in order to provide the efficient clinical and genetic diagnosis of RTT as well as counseling of family with affected children. The data obtained have shown to increase significantly the efficiency of the diagnosis as well as genetic counseling of families with Rett syndrome affected children. Key words: Rett syndrome, x-chromosome inactivation, mecp2 mutations, replication of chromosome x, children.